2019
DOI: 10.1155/2019/1292891
|View full text |Cite
|
Sign up to set email alerts
|

1-Trichloromethyl-1,2,3,4-tetrahydro-beta-carboline (TaClo) Induces the Apoptosis of Dopaminergic Neurons via Oxidative Stress and Neuroinflammation

Abstract: Several in vitro studies have revealed the neurotoxicity of 1-trichloromethyl-1,2,3,4-tetrahydro-beta-carboline (TaClo). However, the underlying mechanism has not been completely elucidated, particularly in vivo. This study was designed to study the neurotoxicity of TaClo in vivo by stereotactically injecting TaClo into the striatum of Wistar rats. After the TaClo injections, rats were subjected to an open field test, and their distance travelled and tracks showed decreasing trends over time. The results of li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…And the results (Figure S10C,D) showed that these proteins were involved in some degenerative disease pathways, such as amyotrophic lateral sclerosis, Parkinson's disease, and Huntington's disease, which were associated with oxidative stress. 24 Quantification of HNE-Sensitive Sites in 293T Cells Using the SILAC-ABPP Strategy. It is reported that different sites exhibit varying sensitivities to HNE modification.…”
Section: Maldi-tof Ms Analysismentioning
confidence: 99%
“…And the results (Figure S10C,D) showed that these proteins were involved in some degenerative disease pathways, such as amyotrophic lateral sclerosis, Parkinson's disease, and Huntington's disease, which were associated with oxidative stress. 24 Quantification of HNE-Sensitive Sites in 293T Cells Using the SILAC-ABPP Strategy. It is reported that different sites exhibit varying sensitivities to HNE modification.…”
Section: Maldi-tof Ms Analysismentioning
confidence: 99%
“… 67 TCE is structurally similar to the MPTP has led to speculation that it could cause PD. 68 TaClo, one of the mitochondrial toxicants, is cytotoxic to the primary culture of dopaminergic neurons, 69 which further induces apoptosis by blocking the transfer of electrons from complex I to ubiquinone in both rat brains homogenates and liver submitochondrial particles. 70 , 71 Similarly, animal models exposed to TCE have shown nigrostriatal degeneration, which led to the mitochondrial dysfunction and the development of parkinsonian features.…”
Section: Mitochondrial Toxicants and Neurodegenerationmentioning
confidence: 99%
“…It inhibited MCI in the SK-N-SH neuroblastoma cell line. Stereotaxic injection of TaClo into the striatum of Wistar rats resulted in impairment of MCI and elevation of ROS . Quinolinic acid (Q) is a metabolite in the kynurenine pathway that inhibits MCI and increases ROS generation.…”
Section: Role Of MCI Dysfunction In Pdmentioning
confidence: 99%
“…Stereotaxic injection of TaClo into the striatum of Wistar rats resulted in impairment of MCI and elevation of ROS. 122 Quinolinic acid (Q) is a metabolite in the kynurenine pathway that inhibits MCI and increases ROS generation. It was also found to promote oligomerization of Tau.…”
Section: Oxidative Stress and MCI Dysfunction Oxidative Stress Arises...mentioning
confidence: 99%